To Pack or Not to Pack: Inpatient Management of Epistaxis in the Elderly. Issue 6 (November 2018) - Zhou, Albert H.; Chung, Sei Y.; Sylvester, Michael J.; Zaki, Michael; Svider, Peter S.; Hsueh, Wayne D.; Baredes, Soly; Eloy, Jean Anderson
Background: Epistaxis is common in elderly patients, occasionally necessitating hospitalization for the management of severe bleeds. In this study, we aim to explore the impact of nasal packing versus nonpacking interventions (cauterization, embolization, and ligation) on outcomes and complications of epistaxis hospitalization in the elderly. Methods: The 2008–2013 National Inpatient Sample was queried for elderly patients (≥65 years) with a primary diagnosis of epistaxis and accompanying procedure codes for anterior and posterior nasal packing or nonpacking interventions. Results: A total of 8449 cases met the inclusion criteria, with 62.4% receiving only nasal packing and 37.6% receiving nonpacking interventions. On average, nonpacking interventions were associated with a 9.9% increase in length of stay and a 54.0% increase in hospital charges. Comorbidity rates did not vary between cohorts, except for diabetes mellitus, which was less common in the nonpacking cohort (26.6% vs 29.0%; P  = .014). Nonpacking interventions were associated with an increased rate of blood transfusion (24.5% vs. 21.8%; P  = .004), but no significant differences in rates of stroke, blindness, aspiration pneumonia, infectious pneumonia, thromboembolism, urinary/renal complications, pulmonary complications, cardiac complications, or in-hospital mortality. Comparing patients receiving ligation or embolization, no differences in length of stay, complications, or in-hospital mortality were found; however, embolization patients incurred 232.1% greater hospital charges ( P  < .001). Conclusion: Nonpacking interventions in the elderly do not appear to be associated with increased morbidity or mortality when compared to nasal packing only but appear to be associated with increased hospital charges and length of stay. Embolization in the elderly results in greater hospital charges but no change in outcome when compared to ligation.